Strategy for Developing a Rice-Fish Farming Business based on Agrotourism in Panembangan Village, Cilongok District, Banyumas Regency - Anggraeni, Wishnu; Watemin, Watemin; Lumongga, Dumasari; Budiningsih, Sulistyani (Indonesian Journal of Agriculture and Environmental Analytics, 2025)
Mina padi, as a form of integrated agriculture that combines rice and fish farming, has dual potential as a food source and an educational tourism object. Although the Mina Padi Panembangan Tourism is the only rice-fish agrotourism in Banyumas and is conceptually a Smart Fisheries Village, its area has shrunk from 25 Ha to 11 Ha, indicating a decline. This research aims to formulate a development strategy for rice-fish integrated agrotourism in Panembangan Village, Cilongok District, Banyumas Regency. This study uses a descriptive qualitative and quantitative approach, with data obtained from 4 internal respondents (managers and farmers) and 50 external respondents (visitors). Data analysis was conducted through three stages: internal (IFE) and external (EFE) environmental analysis, SWOT analysis, and the Analytical Hierarchy Process (AHP) to determine priority strategies. The results of the IFE and EFE analyses indicate that the business position is in Quadrant I, suggesting a highly favorable situation for aggressive growth. Based on the AHP analysis, the main priority strategy is to submit a grant proposal to support the sustainability of activities in the rice-fish farming area for the rice-fish tourism series as an initial step in the growth and development of the rice-fish farming business, with a weight result of 0.192. This strategy is expected to support the sustainable growth and development of the rice paddy-based agrotourism business in Panembangan Village.